استعمالات مصطلح التمويل، والألفاظ ذات الصلة في كتب الفقه الإسلامي القديم، ومقارنته بمفهومه في الاقتصاد الوضعي = Uses of the term finance and related vocabulary in ancient Islamic jurisprudence books in comparison with its concept in economics - Arif, Arif Ali; Hendaoui, Hassan Ben Brahim; Kouadri, Missou (Core Studies Center, Selangor International Islamic Universiti College, 2019)
Economics has witnessed high competition from Islamic finance. Islamic finance has proven superiority over interest financing especially in light of the successive Crises on the global financial system. The success in Islamic finance instigated the application of Islamic Finance in Muslim and non-Muslim countries in financial sector and banking. There is no doubt that the reason for its superiority over its interest based counterpart is due to its dependence on the principles of Islamic law. The development of contemporary economics terminologies has necessitated Islamic scholars and Islamic economics to develop contemporary Islamic Finance concepts. The purpose of development of Islamic economics terminologies is to distinguish it from riba - based financing. This research is intended to reveal the uses of the term Islamic Finance in the books of ancient Islamic Jurisprudence and the relevant vocabulary in comparison with the concept in Islamic jurisprudence and economics. The research will therefore follow the deductive approach to find and track the occurrence of this term of and related terms in the texts of ancient books of Islamic Jurisprudence. The research will also apply comparative approach to compare Islamic Finance concept and riba-based financing. ****************************************************************************** يشهد الاقتصاد العالمي المعاصر منافسة شديدة بين التمويل الإسلامي والربوي، وقد أثبت التمويل الإسلامي تفوقه على نظيره الربوي، ولاسيما في ظل الأزمات المتوالية على النظام المالي العالمي، حيث استدعى من بعض الحكومات في الدول غير المسلمة، وحتى المسلمة منها انتهاجه في المؤسسات المالية والمصرفية الربوية، ولا شك أن سبب تفوقه على نظيره الربوي يرجع إلى اعتماده على مبادئ الشريعة الإسلامية الغرّاء، وقد استدعى تطور المصطلحات الاقتصادية المعاصرة علماء الشريعة الإسلامية، والاقتصاد الإسلامي وضع مفاهيم معاصرة للتمويل الإسلامي وبيان أسسه؛ لتمييزه عن التمويل الربوي، ويأتي هذا البحث للكشف عن استعمالات مصطلح التمويل الإسلامي في كتب الفقه الإسلامي القديمة، والألفاظ ذات الصلة ومقارنتها بمفهومه في الفقه الإسلامي، والاقتصاد الوضعي؛ لذا سينتهج البحث المنهج الاستقرائي؛ للاسقراء وتتبع مواضع وروود هذا اللفظ، والألفاظ ذات الصلة في نصوص من كتب الفقه الإسلامي القديمة، والمنهج المقارن لمقارنته مع مفهوم وأسس التمويل الربوي.